A microbiological study of Papillon-Lefévre syndrome in two patients. Issue 5 (1st May 2001) - Robertson, K L; Drucker, D B; James, J; Blinkhorn, A S; Hamlet, S; Bird, P S
Abstract : Aim —To analyse the microflora of subgingival plaque from patients with Papillon-Lefévre syndrome (PLS), which is a very rare disease characterised by palmar-plantar hyperkeratosis with precocious periodontal destruction. Methods —Bacterial isolates were identified using a combination of commercial identification kits, traditional laboratory tests, and gas liquid chromatography. Some isolates were also subjected to partial 16S rDNA sequencing. Plaque samples were also assayed for the presence of Porphyromonas gingivalis, Prevotella intermedia, and Actinobacillus actinomycetemcomitans in a quantitative enzyme linked immunosorbent assay (ELISA) using monoclonal antibodies. Results —The culture results showed that most isolates were capnophilic and facultatively anaerobic species—mainly Capnocytophaga spp and Streptococcus spp. The latter included S constellatus, S oralis, and S sanguis . Other facultative bacteria belonged to the genera gemella, kingella, leuconostoc, and stomatococcus. The aerobic bacteria isolated were species of neisseria and bacillus. Anaerobic species included Prevotella intermedia, P melaninogenica, and P nigrescens, as well as Peptostreptococcus spp. ELISA detected P gingivalis in one patient in all sites sampled, whereas A actinomycetemcomitans was detected in only one site from the other patient. Prevotella intermedia was present in low numbers. Conclusions —Patients with PLS have a very complex subgingival flora including recognised periodontal pathogens. However, no particular periodontopathogen is invariably associated with PLS.